Malignant fibrous histiocytoma of the tongue - P. Antonová; L. Dzan; A. Šimůnek; L. Vavřičková (Czech Dental Chamber, 2011)
Sarcomas are neoplasm's of mesenchymal origin and represent less than 2% of all cancers. The histological classification is often difficult (there are more than 50 subtypes of sarcoma) and they are characterized according to the tissue from which they develop, with 4/5 arising from soft tissues and 1/5 from bone. Among the most common sarcomas in adults are malignant fibrous histiocytoma (40%) and liposarcoma (25%), less common is osteosarcoma, angiosarcoma, and fibrosarcoma. The most common sarcoma in childhood is rhabdomyosarcoma. Sarcomas can arise anywhere in the body, the most common sites are the extremities (50%), followed by the trunk and retroperitoneum (40%) but only 10% involve the head and neck region.Malignant fibrous histiocytoma (MFH) is an aggressive tumor of soft tissue, mainly affecting the lower and upper extremities, retroperitoneum or abdominal cavity. Primary MFH of soft tissues of the oral cavity is rare (1-3%).Tru-cut biopsy or open biopsy is used to provide material for the histopathological determination of the nature of the tumor. The biopsy technique for quick frozen mesenchymal tumors is not ideal and is burdened by a number of difficulties. A large number of relatively rare sarcoma subtypes place huge demands on the experience and knowledge of the pathologists to determine the correct diagnosis, without which it is not possible to choose the most appropriate treatment strategy. In terms of histological features, of importance are: the degree of Ki 67 (mitotic index), the level of cell differentiation and the presence of necrosis. The histopathological grade correlates with levels of recurrence and overall survival. The authors present an unusual case of extensive malignant fibrous histiocytoma of the tongue, focusing on the histopathological picture.